2014
DOI: 10.1111/evj.12267_85
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of Glycogen Synthase in Equine Type 1 Polysaccharide Storage Myopathy

Abstract: This publication is a compilation of all Research Abstracts presented at the Ninth International Conference on Equine Exercise Physiology. Unlike previous ICEEP conferences there will not be a conference proceedings of full length manuscripts. These abstracts succinctly summarise a wide array of investigations relevant to the equine athlete, and will be useful to veterinarians and others involved in management of horses used for sport, work and competition. The abstracts encompass the topics of Applied Physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, it was suggested that high resolution respirometry might be useful for identifying horses with dysfunctional muscle energy metabolism that might subsequently develop ER . Biopsies were taken from the semimembranosus muscle to measure glycogen synthase (GS) activity in Belgian draught horses which were PSSM1 homozygotes, heterozygotes or controls . Glycogen synthase activity was significantly higher in PSSM1 homozygotes than in heterozygotes and control horses but was not associated with increased expression or degradation of the mutant enzyme.…”
Section: Muscle Physiologymentioning
confidence: 99%
“…Furthermore, it was suggested that high resolution respirometry might be useful for identifying horses with dysfunctional muscle energy metabolism that might subsequently develop ER . Biopsies were taken from the semimembranosus muscle to measure glycogen synthase (GS) activity in Belgian draught horses which were PSSM1 homozygotes, heterozygotes or controls . Glycogen synthase activity was significantly higher in PSSM1 homozygotes than in heterozygotes and control horses but was not associated with increased expression or degradation of the mutant enzyme.…”
Section: Muscle Physiologymentioning
confidence: 99%